Pengelolaan Biaya Modal Kerja Pendidikan Di Mdta Sukma Illahi 3 Suku Canduang - Alhamda, Robi; Karim, Hamdi Abdul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore the strategy of working capital cost management in educational institutions using a literature study approach. The working capital cost of education includes funds needed to fund the daily operational activities of educational institutions, such as salaries of educators, procurement of teaching materials, and maintenance of facilities and infrastructure. This study identifies four important aspects in the management of working capital costs of education, namely planning, allocation, supervision, and sources of financing. The results of the study indicate that effective management of working capital costs can improve operational efficiency and the quality of educational services. This article provides important implications for leaders of educational institutions in making appropriate short-term financial decisions to support the continuity of educational activities. This study also reflects the real conditions at MDTA Sukma Illahi 3 Suku Canduang as an example of an educational institution facing similar challenges